If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (90 + -1x) = 5x Remove parenthesis around (90 + -1x) 90 + -1x = 5x Solving 90 + -1x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 90 + -1x + -5x = 5x + -5x Combine like terms: -1x + -5x = -6x 90 + -6x = 5x + -5x Combine like terms: 5x + -5x = 0 90 + -6x = 0 Add '-90' to each side of the equation. 90 + -90 + -6x = 0 + -90 Combine like terms: 90 + -90 = 0 0 + -6x = 0 + -90 -6x = 0 + -90 Combine like terms: 0 + -90 = -90 -6x = -90 Divide each side by '-6'. x = 15 Simplifying x = 15
| m^2+mn-56n^2=0 | | 5x=(90-x) | | -3n=29 | | -6g+20=-10g | | 43=-9-14x | | 12x+5=149 | | 10y-8y-y=0 | | x^2+8x=2x^2-40 | | .4x+4=40 | | 20-8=x/3 | | 1800+450=600p+1200 | | 5(x+4)+2=5x+2 | | (x^2-4x+16)(x+4)=0 | | 43=-9-14r | | 25x+16=40x | | 38.72+23.19+n=31.18 | | 22x-6-16x+4=18x-8-12x+15 | | 5y-26=-6(y+8) | | -2-10y+11y=-4 | | 17=-1-9a | | 4-0.7(p-3)=0.2(4p-3) | | 15+4x=5x+5 | | -9+x=.875x-23 | | -4x-4x=46-6 | | X^2+8x=2x^2+2x-40 | | X^12=9 | | yx+6x=7 | | 3/x^3-27 | | 12s-5-11s=-3+3 | | -9d-19=-11d+19 | | x^2+y^2-6x-16y+57=0 | | yx+6y=7 |